2021
DOI: 10.33682/xdpq-bwp2
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Validating the International Social and Emotional Learning Assessment: Evidence from a Pilot Test with Syrian Refugee Children in Iraq

Abstract: The growing focus on social and emotional learning (SEL) for children of primary grade age in conflict-affected and fragile contexts necessitates an understanding of the effects these programs have. However, the dearth of valid and reliable measures of SEL skills in low-resource and crisis contexts has constrained the generation of this evidence. The few tools that have robust psychometric properties were developed for use in high-resource contexts; they often have usage costs, limit adaptations, and focus on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…At Wave 5, children reported on four risk factors from the International Social Emotional Learning Assessment, which was developed and tested in Uganda and Kenya (ISELA; D’Sa, 2019) and captured children’s lifetime exposure to different types of risk factors. For each of the four risk factors, we created a binary indicator variable (0 = no, 1 = yes).…”
Section: Methodsmentioning
confidence: 99%
“…At Wave 5, children reported on four risk factors from the International Social Emotional Learning Assessment, which was developed and tested in Uganda and Kenya (ISELA; D’Sa, 2019) and captured children’s lifetime exposure to different types of risk factors. For each of the four risk factors, we created a binary indicator variable (0 = no, 1 = yes).…”
Section: Methodsmentioning
confidence: 99%
“…A review by Halle and Darling‐Churchill ( 2016 ) identified six SEL measurement tools having strong psychometric properties, all of which had been validated for use only in WEIRD contexts. More recently, two SEL assessments have been validated in populations of Syrian refugees—the International Social‐Emotional Learning Assessment measure of five domains of SEL in Iraq (D’Sa & Krupar, 2019 ), and the Social‐Emotional Response and Information Scenarios in Lebanon (Kim & Tubbs Dolan, 2019 ). Halpin et al ( 2019 ) also found that the SEL domain in the International Development and Early Learning Assessment had the same factor structure across five countries: Afghanistan, Bolivia, Ethiopia, Uganda, and Vietnam.…”
Section: Current Approaches To Measuring Sel Across Contextsmentioning
confidence: 99%
“…Evidence on the impact of SEL initiatives with refugee communities is significantly lacking (USAID, 2022) and it remains unclear if and how SEL functions as a tool of cultural imperialism, Westernization, or otherwise. As a result, some scholars have attempted to explore the effects of SEL with refugee and crisis-affected communities (Diazgranados Ferráns et al, 2019;D'Sa & Krupar, 2021;Torrente et al, 2019;. However, much of this work is largely quantitative and preoccupied with the measurement of Western SEL skills and academic achievement, rather than the interrogation of the Western assumptions and post-colonial logics that underly many SEL initiatives in refugee and crisis contexts.…”
Section: Problematizing Western Selmentioning
confidence: 99%